Object-oriented mathematical modeling for estimating electric vehicle’s range using modelica (2018)
Electric vehicles (EVs) offer a great alternative for decarbonizing the transport sector. However, insufficient recharging infrastructure and limited range increase the driver’s ‘range anxiety’. Furthermore, the autonomy information provided by vehicle manufacturers differs from the range obtained under real-driving conditions. In order to estimate the actual range of an EV under different driving profiles, accurate computational modeling is required. This paper presents a library for modeling and simulating EVs using the object-oriented modeling language Modelica that allows calculating the energy consumption and the impact of different driving behaviors on the vehicle’s driving range. Each vehicle’s model only requires generic parameters that can be obtained from the vehicle’s manufacturer’s specification sheet. The parameters of the example models have been calibrated using vehicle parameters found in the literature for several commercial vehicles. © Springer Nature Switzerland AG 2018.